Notes on the Caribbean Essay from an Archipelagic Perspective (Kamau Brathwaite, Édouard Glissant and Antonio Benítez Rojo) - Bonfiglio, Florencia (2015)
The article analyzes the construction of a Caribbeanist discourse in the region’s cultural essay by looking at the work of three recognized authors from three different linguistic blocs: Édouard Glissant (1928- 2011), Antonio Benítez Rojo (1931-2005) and Kamau Brathwaite (1930-). According to the drive for symbolic integration that their essays on Caribbean culture show, the region’s literature constitutes itself as a complex weave of shared symbols, figures and notions and a dense network of intellectual relations which crosses linguistic and national barriers. It is the production of an essay “in a certain kind of way” that the writers share: an “archipelagic” kind of way in which the recurrence of aquatic metaphors—a legacy from founders of Caribbeanness like Aimé Césaire—allow writers to inscribe a regional (decolonizing) imprint in postmodern thought, affiliating themselves—even when the revolutionary spirit is long gone—with the decolonizing thrust of “the long sixties.”